Evaluation of Real-World Quality of Asthma Care According to the Spanish Consensus Protocol: The AsmaNET Project (ESR-20-20897) - Dominguez-Ortega J; Narváez-Fernández E; Ramos J; Cancelliere N; García-Criado J; Sanchez-Ocando H; Gallardo-Higueras A; Dávila I (Journal of Asthma and Allergy)
Javier Dominguez-Ortega,1,2 Emilio Narváez-Fernández,1 Jacinto Ramos,3 Nataly Cancelliere,4 Jorge García-Criado,5 Humberto Sanchez-Ocando,1 Alicia Gallardo-Higueras,6 Ignacio Dávila6,7 1Department of Allergy, Hospital Universitario La Paz, Madrid, Spain; 2Institute for Health Research, IdiPAZ, Madrid, Spain; 3Pulmonology Service, University Hospital of Salamanca, Salamanca, Spain; 4Department of Emergency Medicine, Hospital Universitario La Paz, Madrid, Spain; 5Department of Emergency Medicine, University Hospital of Salamanca, Salamanca, Spain; 6Allergy Service, University Hospital of Salamanca, Salamanca, Spain; 7Department of Biomedical and Diagnosis Sciences, Faculty of Medicine, University of Salamanca, IBSAL, Salamanca, SpainCorrespondence: Javier Dominguez-Ortega, Department of Allergy, Hospital Universitario La Paz, Paseo de la Castellana 261, Madrid, 28046, Spain, Email javier.dominguez@idipaz.esBackground: The emergency room (ER) approach for patients with asthma exacerbations (AEs) should be based on a comprehensive, multidisciplinary approach to ensure effective and timely care. This study aims to analyze the compliance level of recommended indicators, as defined in a consensus document, for the management of AEs in the ER using available electronic medical records.Methods: An open-label, observational, non-interventional, retrospective study of adult patients treated in hospital ER for AEs was conducted at La Paz University Hospital and Salamanca University Hospital. Data were collected from medical records regarding a set of predefined measures and variables concerning asthma severity, ER stay, and subsequent discharge.Results: During 2019, a total of 1,019 patients accounted for 1,089 AEs were evaluated. Clinical variables predominantly included historical data, such as previous hospitalizations, Intensive Care Unit admissions, and prior exacerbations, which were recorded in 45.8% of medical records. Auscultation details were extensively documented (99.8%), yet respiratory rate (25.4%) and spirometry (less than 10%) were notably lower. Regarding discharge planning, 69.6% of patients had a defined care plan, and 59.5% received Inhaled Corticosteroids plus Long-Acting Beta-Agonists combination treatment at discharge. Medical referrals resulted in 25.5% being referred for specialized care and 87.2% to primary care. 13.3% had a specific post-discharge care timeframe.Conclusion: This study highlights significant variability in the documentation and adherence to recommended indicators for AE management in the ER. Moreover, discharge planning and follow-up care were suboptimal. These findings underscore the need for improved standardization and implementation of evidence-based protocols in emergency asthma care.Keywords: asthma exacerbation, emergency room management, electronic medical records, quality indicators